Morale, Relationships, and Wages: An Experimental Study - Florian Englmaier; Carmit Segal (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Many labor relations are characterized by the possibility of repeated interaction without long term contracts and with discretionary pay components. We implement such a structure in the lab by allowing workers and firms to interact repeatedly for many periods absent a pre-announced final period. In this setting persistent and different human resource practices emerge endogenously: we find (long-term) relationships characterized by generous surplus sharing and spot-interactions with little to no rent for the workers. Efficiency, i.e. exerted effort, is comparable across these two institutions. Hence, spot-interactions are at least as profitable for firms engaging in such relationships. In control treatments, we show that neither limited firm commitment nor structural unemployment alone is sufficient to generate these patterns. Analyzing individual level data, we document that firm and worker behavior are individually rational and that individual histories play a significant role in explaining the observed behavior.
Keywords: C91; D21; M50; 330